Upland Rice Logistics and Supply Chain Management in Kanchanadit District, Surat Thani Province - Nuprain, Ampawan; Srikarn, Mathinee; Jundum, Siriprapa (Journal of Management Sciences Suratthani Rajabhat University, 2023)
The logistics and supply chain management of upland rice agriculturalists is a beneficial process for agriculturists because every activity is important to make it worthwhile in upland rice production. Operation process is relevant to downstream, midstream and upstream. This research aimed to study the relationship of stakeholders in upland rice logistics and supply chain by analyzing problems, and obstacles of stakeholders that are relevant to upland rice logistics and supply chains and to set guidelines for logistics development and upland rice supply chain. This research was a quantitative analysis using interview. The purposive sample was used to select 18 upland rice agriculturers and 4 upland rice agriculturalist supporters. The results showed: 1) the relationship of stakeholders in upland rice logistics and supply chain; 2) Productivity problem did not meet the target; 3) Guidelines for logistics development and upland rice supply chain of agriculturalists should collect data on increasing yield rate per rai in each planting cycle and method to deal with harvesting process according to principles of logistics management. The results could be used to formulate a community development policy plan in food sustainability development in order for the systematic local community development plan to develop the quality of life of people in the community.